2016
DOI: 10.1002/jbm.b.33814
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic potential of stem cells‐seeded bioactive nanocomposite scaffolds: A comparative study between human mesenchymal stem cells derived from bone, umbilical cord Wharton's jelly, and adipose tissue

Abstract: Bone regeneration is considered as an unmet clinical need, the aim of this study is to investigate the osteogenic potential of three different mesenchymal stem cells (MSCs) derived from human bone marrow (BM-MSCs), umbilical cord Wharton's jelly (UC-MSCs), and adipose (AD-MSCs) seeded on a recently developed nanocomposite scaffold (bioactive glass/ gelatin) implanted in rat animal models with critical size calvarial defects. In this study, after isolation, culture, and characterization, the MSCs were expanded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
66
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(70 citation statements)
references
References 40 publications
2
66
1
1
Order By: Relevance
“…Johari et al (2016b) reported that the bioglass/gelatin scaffold had no cytotoxicity for osteoblast cells. In addition, similar results were obtained from cytotoxicity studies of different nanocomposites on the MSCs, osteoblasts and endothelial cells (Azami et al, ; Johari et al, ; Samadikuchaksaraei et al, ; Kargozar et al, ).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Johari et al (2016b) reported that the bioglass/gelatin scaffold had no cytotoxicity for osteoblast cells. In addition, similar results were obtained from cytotoxicity studies of different nanocomposites on the MSCs, osteoblasts and endothelial cells (Azami et al, ; Johari et al, ; Samadikuchaksaraei et al, ; Kargozar et al, ).…”
Section: Discussionsupporting
confidence: 69%
“…About 70% of the bone structure is composed of nanocrystalline HA, which makes this substance one of the main mineral components for fabrication of a substitute, which mimics the bone structure and the microenvironment. To mimic the organic component of the bone and optimize the mechanical properties, HA is usually used in the composite form with polymeric components such as gelatin (Samadikuchaksaraei et al, ; Kargozar et al, ). In this case, another strategy was also adopted to increase the regenerative properties of the microenvironment provided by the bone scaffolds via incorporation of silicon nitride into the body of the scaffold (Munoz et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of Bioglass and its dissolution products on stem cells is less clear and there is some contradictory evidence in the literature. Osteogenic differentiation of human bone marrow stem cells (hMSCs) in contact with BGs was investigated [47][48][49][50][51][52][53], but results varied depending on the particular types of stem cells tested. Some articles found no effect on stem cells in vitro: Bioglass 45S5 did not stimulate the alkaline phosphatase (ALP) activity of hMSCs from five different human donors [54] and a Bioglass 45S5 coating on a polymeric substrate had no direct effect on osteoprogenitor cell differentiation or bone formation [55].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies examining the combination of MSCs and 3-D scaffolds in bone regeneration have reported promising outcomes in animal critical size bone defects [38-43]. These studies aimed to achieve the final result of bone repair by using different kinds of scaffolds [44], sources of MSCs [45] or loaded factors [46-48], but very few studies have focused on the role of the seeded cells.…”
Section: Discussionmentioning
confidence: 99%